2003
DOI: 10.1641/0006-3568(2003)053[0341:tnc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Nitrogen Cascade

Abstract: Human production of food and energy is the dominant continental process that breaks the triple bond in molecular nitrogen (N 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
1,636
0
50

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,538 publications
(1,760 citation statements)
references
References 104 publications
13
1,636
0
50
Order By: Relevance
“…Nitrogen is a major nutrient that controls primary productivity in many coastal waters, and atmospheric deposition is an important non-point source of both organic and inorganic nitrogen (Ryther and Dunstan, 1971;Vitousek and Howarth, 1991;Nixon, 1995;Paerl, 1995;Paerl and Whitall, 1999;Seitzinger and Sanders, 1999;Rabalais, 2002;Driscoll et al, 2003;Galloway et al, 2003). Excessive fluxes of nitrogen from atmospheric sources result in the eutrophication of many coastal waters in the United States, which is now considered the most widespread water quality problem (Nixon, 1995;Carpenter et al, 1998 (Psuty et al, 1993;Zampella et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen is a major nutrient that controls primary productivity in many coastal waters, and atmospheric deposition is an important non-point source of both organic and inorganic nitrogen (Ryther and Dunstan, 1971;Vitousek and Howarth, 1991;Nixon, 1995;Paerl, 1995;Paerl and Whitall, 1999;Seitzinger and Sanders, 1999;Rabalais, 2002;Driscoll et al, 2003;Galloway et al, 2003). Excessive fluxes of nitrogen from atmospheric sources result in the eutrophication of many coastal waters in the United States, which is now considered the most widespread water quality problem (Nixon, 1995;Carpenter et al, 1998 (Psuty et al, 1993;Zampella et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Humans create more reactive N (Nr) than natural ecosystems do (Galloway et al 2003), principally nitrogen oxides (NO x -N, i.e., sum of N 2 O, NO, and NO 2 ) and ammonia (NH 3 ), mostly through food and energy production and consumption, and their various byproducts. Reactive N Fig.…”
Section: Increased Anthropogenic Nitrogen Emissionsmentioning
confidence: 99%
“…In contrast, further increases in N emissions in the East Asia region during the next few decades have been predicted as a consequence of rapid industrialization, urbanization, and economic growth (e.g., Galloway et al 2003Galloway et al , 2004Fang et al 2011). Fang et al (2011 indicated that N deposition in China ranged 2.6-48 kg N ha -1 year -1 , while the threshold of N deposition to N saturation in Chinese forest differs from that in the USA and Europe (i.e., the relatively high N leaching in some Chinese forests receiving low N-input).…”
Section: Long-term Effects Of N Deposition In Watershed N Cycles Andmentioning
confidence: 99%
“…dead zones in coastal areas) and terrestrial ecosystems and making contributions to climate forcing in the form of nitrous oxide (N2O) (30,31).…”
Section: Text Boxmentioning
confidence: 99%